2021
DOI: 10.37934/cfdl.13.1.7283
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis of Rigs-to-Reefs (R2R) Jacket Structures

Abstract: Platform decommissioning activities have been increasing due to unproductive fields and unstable oil prices. One of the decommissioning methods used by the oil and gas companies is by converting the platform into an artificial reef through the rigs-to-reef (R2R) programme. The programme benefits the marine life and increases the marine productions. In this study, the dynamic responses and flow characteristics of jacket platforms were investigated using computational fluid dynamics (CFD) analysis. Three jacket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, it was only in 2021 that a geometric model of a platform jacket converted to a RA was used in CFD studies conducted by Rahman et al, [11,12]. In these works, the efficiency of the sinking method (that is, the direction in which the jacket is tipped) in terms of upwelling and back vortex generation are explored, as well as other parameters, such as drag, lift forces and pressure distribution.…”
Section: Introduction 11 Purpose and Motivationmentioning
confidence: 99%
“…Nevertheless, it was only in 2021 that a geometric model of a platform jacket converted to a RA was used in CFD studies conducted by Rahman et al, [11,12]. In these works, the efficiency of the sinking method (that is, the direction in which the jacket is tipped) in terms of upwelling and back vortex generation are explored, as well as other parameters, such as drag, lift forces and pressure distribution.…”
Section: Introduction 11 Purpose and Motivationmentioning
confidence: 99%
“…The study shows that the lateral displacement has decreased significantly, and that the displacement and acceleration between floors are clearly reduced, and the study confirmed the use of the isolation method in the ground floor to improve the seismic capacity of the structures. Also, many research was done for computational fluid dynamics (CFD) to study the dynamic movement of water wave to the offshore platform [6][7][8][9]. Fernando R. and Roger M. [10] applied CFD techniques for the sunk jacket in the seabed by using ANSYS software and the finite volume method.…”
mentioning
confidence: 99%